Barium Titanate Nanostructures and Thin Films for Photonics. Issue 24 (5th November 2020) - Karvounis, Artemios; Timpu, Flavia; Vogler‐Neuling, Viola V.; Savo, Romolo; Grange, Rachel
Abstract: Barium titanate (BaTiO3 ) is a synthetic crystal used in electromechanical transducers and multilayer ceramic capacitors. Since it is not available in nature, a variety of growth methods has been employed to produce in large scale, with high quality and low‐cost. BaTiO3, as a metal oxide meets practical requirements such as physical hardness, stability and tunable optoelectronic properties. The plethora of characteristics renders it functional in diverse fields of applications from energy harvesting to biophotonics. Related to optical properties, it is a dielectric material from the near ultraviolet to the near‐infrared part of the spectrum with low optical losses and relatively high refractive index. The strong second‐order nonlinear response has resulted in several breakthroughs in bioimaging, while its intrinsic electrooptic response is among the highest within the existing materials. The properties of the BaTiO3 may also be modified by doping or hybridization with other materials. This review presents the basic optoelectronic properties of BaTiO3, reports on the recent advances in BaTiO3 nanostructures and thin films related to photonic applications, and oversees photonic technologies that may benefit from this material platform in the near future. Abstract : The progress in various photonic applications based on barium titanate nanostructures and thin films is presented. Barium titanate is a noncentrosymmetric crystal that offers opportunities to develop advanced photonic nanodevices through bottom‐up or top‐down fabrication methods. The low optical losses, the large electrooptic response, the intrinsic second‐order nonlinearity, and the tunable optoelectronic properties render a material platform of high interest.